Ecological features of the vermicomposting process: meta-analysis - Lemiasheuski, Viktar; Yan, Li; Maksimova, Svetlana (Journal of the Belarusian State University. Ecology, 2024)
In order to comprehensively assess the compost quality and heavy metal transformation patterns of vermicomposting under various control conditions, we reviewed 109 articles. Through meta-analysis, we quantitatively investigated the effects of vermiculture species, pre-composting duration, ventilation methods, initial C/N ratio, initial pH, and initial moisture content on improving compost quality and reducing heavy metal toxicity. The results indicate that all six grouping factors significantly influence compost quality and heavy metal toxicity. After vermicomposting, the following nutrient indicators significantly increased: NO3–N (increased by 116.2%), total nitrogen (increased by 29.1%), total phosphorus (increased by 31.2%), and total potassium (increased by 15.0%). Meanwhile, NH4+-N content (decreased by 14.8%) and C/N ratio (decreased by 36.3%) significantly decreased. Additionally, the total amounts and bioavailability of copper and chromium in the final compost also significantly decreased. Considering the significant effects of different grouping factors on compost quality and heavy metal impact, if the primary objective of composting is to promote decomposition and nutrient enrichment, it is recommended to adjust the initial moisture content of composting materials to 70%-80%, C/N ratio to 30-85, and pH to 6-7, and conduct pre-composting for 315 days with natural ventilation. If the main goal is to mitigate heavy metal hazards in the materials, it is advisable to adjust the initial moisture content to 50%-60%, C/N ratio below 30, pH to 7-8, skip pre-composting, turn the pile regularly, and employ the Eudrilus eugeniae species for vermicomposting. These recommendations will facilitate the comprehensive utilization of chicken manure, earthworms, and Chinese herbal residue, optimizing the compost-ing process.